2019
DOI: 10.17503/agrivita.v41i1.1787
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Biological and Chemical Fungicides to Control White Rust in Chrysanthemum Grown Under Open Condition

Abstract: The effort to reduce chemicals has become an important issue in floriculture agribusiness. The chemicals included fungicides for white rust control in chrysanthemum. The combined application of synthetic fungicide with biological agent and botanical fungicide were expected not only to reduce synthetic fungicide application, but also suppressed the white rust attacks. The research was conducted at the Indonesian Ornamental Crops Research Institute (IOCRI). A factorial randomized complete blocked experiment was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Greater suppression referred to lesser damages on leaf tissues, thus increased potential leaf area for photosynthesis to support plant growth and flower development (Jones, Parrella, & Hodel, 1986), including the number of marketable flower, though the effects were less visible on flower diameter. The growth improvement and yield as results of botanical pesticide application were also reported in chrysanthemum (Rahardjo, Budiarto, & Marwoto, 2019), citrus (Shinde et al, 2017), tomato (de Evert, López, & de López, 2015, coffee (Alves et al, 2013), other economically important crops.…”
Section: Plant Growth Performance and Flower Productionmentioning
confidence: 67%
See 1 more Smart Citation
“…Greater suppression referred to lesser damages on leaf tissues, thus increased potential leaf area for photosynthesis to support plant growth and flower development (Jones, Parrella, & Hodel, 1986), including the number of marketable flower, though the effects were less visible on flower diameter. The growth improvement and yield as results of botanical pesticide application were also reported in chrysanthemum (Rahardjo, Budiarto, & Marwoto, 2019), citrus (Shinde et al, 2017), tomato (de Evert, López, & de López, 2015, coffee (Alves et al, 2013), other economically important crops.…”
Section: Plant Growth Performance and Flower Productionmentioning
confidence: 67%
“…Several authors also reported the effectivity of Chinese mahogany leaf extract, C. pyrethrum petal extract and Chinaberry leaf extract in controlling many insect pests in several economically important crops though in different concentrations (Ahmadi, Amiri-Besheli, & Hosieni, 2012;Ateyyat & Abu-Darwish, 2009;El-Wakeil, 2013;Pavela, 2009;Shawan, Rashed, Mitu, & Jahan, 2018;Xavier et al, 2015;Zhong, Lv, & Qin, 2017). Greater supression of these botanical extracts also indicated that these potential substances should furtherly be assesed for their efficacy, proper formulation and concentrations, and application in regards to be the alternative and complementary eco-friendly substances from the existing methods and/or commercial biopesticides (Rahardjo, Budiarto, & Marwoto, 2019) to control leafminer in chrysanthemum.…”
Section: Level Of Treatment Efficacymentioning
confidence: 99%
“…The chemicals employ even in the absence of the symptoms and intensity of the diseases to assure the marketable flower quality. In long and frequent applications, these costly practices increased production cost, induced pathogen resistance, and made the chemicals no longer effective (Mahish & Ghritlahare, 2017;Rahardjo et al, 2019;Singh & Vijay, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The disease intensity and severity depended on genotype resistances and environmental conditions. High humidity coupled with warmer temperature might induce a conducive Copyright © 2019 Universitas Brawijaya circumstance for the pathogen to develop rapidly in susceptible cultivars (Bonde et al, 2015;Rahardjo, Budiarto, & Marwoto, 2019).…”
Section: Introductionmentioning
confidence: 99%